Effects of crop sanitation on banana weevil, Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae), populations and crop damage in Uganda - Masanza, M.; Gold, C.; Huis, A. van; Ragama, P.E. (2006)
Crop sanitation, i.e. destruction of crop residues, has been hypothesized to lower banana weevil damage by removing adult refuges and breeding sites. Although it has been widely recommended to farmers, limited data are available to demonstrate the efficacy of this method. The effects of crop sanitation on banana weevil populations and damage were studied in an on-station trial in Uganda. Treatments included low, moderate and high levels of sanitation. Banana weevil populations, estimated by trapping and mark and recapture methods, were lowest in the high sanitation treatment. However, banana weevil damage was either not significantly different among treatments or lower in low sanitation treatments. Similarly, increases in crop sanitation level were not reflected in higher yields. The data from this trial suggest that crop sanitation is not an effective means of managing banana weevil and contrasts with results from an on-farm study in which sanitation reduced both weevil numbers and damage. Possible factors explaining the different outcomes of the two studies are discussed.